(untitled) (Modern education and development, 2025)
Diseases of the larynx occupy one of the leading places among the pathologies of the ENT organs. They include benign and malignant tumors, congenital and acquired pathology of ligamentous, muscular and nervous apparatus. Patients with urgent laryngeal diseases are the most severe of all ENT patients requiring emergency care. 50% of all deceased patients with urgent diseases of ENT organs are patients with laryngeal diseases.